Pengembangan Media Pembelajaran PUT3 Group Pada Pembelajaran Tematik Sekolah Dasar - Nova Ika Ayu Saputri; Minto Santoso; M.Iqbal Baihaqi (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
. Based on initial research at SDN Kaligrenjeng 01, it was found that thematic learning was still considered difficult to implement due to several factors, including, educators dominated more during the learning process and learning media were rarely used during the learning process. The aim of the research is to explain the development, explain the use and learning achievements of students in using PUT3 Group learning media in elementary school thematic learning. The results of learning media validation can be seen from the percentage results by material expert validators, media experts and language experts respectively. 80.00%, 92.50%, and 96.00%, the average validator assessment is 89.36% so that the learning media is suitable for use. Educators' response to the media was 84.00% and students' response to the media was 94.89%. The increase in the average value of students before using the media and after using the media was 75.79%, this shows that there was an increase in the average value of the class, so that the PUT3 Group media was stated to be able to improve students' learning achievement. Based on the research results, it was concluded that the media PUT3 Group learning in elementary school thematic learning is suitable for use. The results of the responses from educators and students show that the PUT3 Group media is easy to use. PUT3 Group learning media in elementary school thematic learning can improve student learning achievement.